Efectividad de la tierra de diatomeas como coadyuvante en aplicaciones foliares de agroquímicos en maíz - Agurto Villacis, Xiomara Carolina (2024)
The objective of this study was to evaluate the effectiveness of diatomaceous earth as an adjuvant in foliar applications of agrochemicals in maize. The treatments evaluated were T1 (Foliar application of agrochemicals with diatomaceous earth), T2 (Foliar application of agrochemicals with a conventional adjuvant), T3 (Foliar application of agrochemicals with water), T4 (Foliar application of diatomaceous earth), and T5 (control treatment). The main variables recorded were grain yield (kg ha-1), fall armyworm damage intensity (%), and foliar spot severity (%). The evaluated treatments significantly influenced grain yield, fall armyworm damage, and foliar spot severity, with treatment T1 achieving the highest yield, and the lowest damage and severity from fall armyworm and foliar spots, respectively, although it was statistically similar to treatments T2 and T3. Treatment T4 did not match the effect of treatments T1, T2, and T3, but was more effective than T5, which showed greater fall armyworm damage and foliar spots. The results indicate that diatomaceous earth can replace conventional adjuvants to enhance the effect of foliar agrochemicals, with the added benefit of promoting greater health and yield in hard yellow maize.